Development of a blocking latex agglutination test for the detection ofantibodies to chicken anemia virus - Trinha, Dai Quang; Ogawa, Haruko; Nghia Bui, Vuong; Thi Hong Nguyen, Tham; Gronsang, Dulyatad; Baatartsogt, Tugsbaatar; Kahoza Kizito, Mugimba; Abo Elkhair, Mohammed; Yamaguchi, Shigeo; Nguyen, Viet Khong; Imai, Kunitoshi (Journal of virological methods, 2015)
tA blocking latex agglutination test (b-LAT) developed in this study was evaluated for the detection ofantibodies against chicken anemia virus (CAV) in chickens. Polystyrene latex beads were coupled witha neutralizing monoclonal antibody (mAb) to CAV (mAb-beads). When mAb-beads were mixed withantigens prepared from the lysate of MDCC-MSB1 cells infected with CAV, agglutination occurred. A shortpre-incubation of CAV antigens with CAV-specific antiserum inhibited the agglutination of mAb-beads.The test results were obtained within 5 min. The specificity of b-LAT was evaluated using sera from specificpathogen-free chickens and sera containing antibodies to avian influenza virus, Newcastle disease virus,infectious bursal disease virus, and Marek’s disease virus; nonspecific agglutination and cross-reactivitywith antibodies to unrelated viruses were not observed. The examination of 94 serum samples collectedfrom commercial breeder chickens of various ages (17–63 weeks) revealed good agreement (93.6%, Kappavalue = 0.82) between b-LAT and a virus neutralization test, known to be most sensitive and specific inthe detection of antibodies to CAV. These results indicate that b-LAT, a simple and rapid test, is a usefuland reliable tool in CAV serology.
Keywords: Chicken anemia virus; Serum antibody; Blocking latex agglutination test; Monoclonal antibody